2013
DOI: 10.1111/ejed.12034
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Institutional Context, Education and Labour Market Policies on Early School Leaving: a comparative analysis ofEUcountries

Abstract: This article presents a comparative analysis of the determinants of early school leaving (ESL) at the country level. We decompose ESL rates into two components: a ‘primary’ rate reflecting unqualified school leaving from initial education, and a second component accounting for early school leavers who participate in training programmes. Both may be influenced by structural and policy determinants. We examine how the ESL rate is affected by macro‐economic and social context variables such as GDP/capita, growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 46 publications
1
36
0
9
Order By: Relevance
“…Additionally, De Witte et al (2013) found a negative relationship between early school leaving and the age of compulsory education. They argue that the longer pupils are obliged to stay in school, the greater the chances that they will graduate (Cabus & De Witte, 2011).…”
Section: Truancy and The Educational Systemmentioning
confidence: 98%
“…Additionally, De Witte et al (2013) found a negative relationship between early school leaving and the age of compulsory education. They argue that the longer pupils are obliged to stay in school, the greater the chances that they will graduate (Cabus & De Witte, 2011).…”
Section: Truancy and The Educational Systemmentioning
confidence: 98%
“…Since the development of the status attainment model (Blau & Duncan, 1967) and the Wisconsin model of education and early occupation attainment (Haller & Portes, 1973), a strong, positive association between education, social origin and individual occupation has been found (Kerckhoff, 2001;Carbonaro, 2007). Higher education attainment is also associated with higher earnings and incomes (Harmon et al, 2003;Barone & Van de Werfhorst, 2011;Hanushek et al, 2013), better health, a higher level of wellbeing and political participation (Oreopoulos & Salvanes, 2011;Braga et al, 2013;De Witte et al, 2013;Hoskins et al, 2014).…”
Section: Educationmentioning
confidence: 99%
“…and the Wisconsin model of education and early occupation attainment(Haller & Portes 1973), a strong, positive association between education, social origin and individual occupation has been found(Kerckhoff 2001;Carbonaro 2007). Higher education attainment is also associated with higher earnings and incomes(Barone & Van de Werfhorst, 2011;Hanushek et al, 2013;Harmon, Oosterbeek, & Walker, 2003), better health, a higher level of wellbeing, and political participation(De Witte et al 2013;Braga et al 2013;Oreopoulos & Salvanes 2011;Hoskins et al 2014).…”
mentioning
confidence: 97%